The effect of maternal-fetal attachment education on pregnant women’s mental health - Perwitasari Perwitasari; Mohammad Hakimi; Anjarwati Anjarwati (Universitas Aisyiyah Yogyakarta, 2019)
Physiological and psychological changes in pregnancy have a considerable effect on mother’s wellbeing. Hence, in this period pregnant women are vulnerable to develop mental health difficulties due to hormonal alterations and other external factors. Mental health problems during pregnancy may impact to child’s growth and psychological development. The aim of this study was to determine the effect of maternal-fetal attachment (MFA) education on the scores of mental health disorders among pregnant women. This study was quasy-experimental. The sample were 55 pregnant women (28=control group, 27=experimental group) who registered in Community Health Centers. Participants were selected by consecutive sampling technique. Data collection tools were EPDS, SRQ, SSQ-6, and demographic questionnaire. These questionnaires were filled out by both groups as pre-test and two weeks later. The data were analyzed by paired and independent t-test in SPSS/20 with significant levels p0,05). This study indicated that maternal-fetal attachment education might contribute in improving pregnant women’s mental health. The future study should be tested in larger sample sizes with more than two weeks follow up to confirm these results.